Technology, Property Rights in Information, and Securities Regulation - Paul G. Mahoney (Washington University Law Quarterly, 1997)
This Article will make three observations about the impact of technology on securities markets and securities regulation. First, the cost of transmitting, storing and manipulating data is a very minor component of the social cost of mandatory corporate disclosure; therefore, the welfare effects of mandatory disclosure are not very sensitive to advances in IT. Second, the traditional intermediaries of securities markets, such as brokers, dealers, and exchanges, serve a variety of purposes besides matching buyers and sellers. Third, advances in IT are unlikely to eliminate informational asymmetries in the securities markets directly through the transmission of data to traders; instead, they will alleviate asymmetries indirectly by making arbitrage more effective and prices more informative.
Keywords: Electronic trading of securities